Book review: Fullbrook, E. and Morgan, J. (2020), Modern monetary theory and its critics - Jahangir, Junaid (My University, 2022)
The book edited by Fullbrook and Morgan is a collection of articles published in Issue 89 of the journal, Real-World Economics Review. It assembles eighteen articles from experts who offer their vision or criticism of Modern Monetary Theory (MMT) that has been popular in the media given fiscal austerity, stagnating wages, rising inequality, and climate change. This review focuses on salient ideas that could be presented to economics students in a way that would challenge mainstream viewpoints including that budget deficits crowd out private investment, that government spending is constrained by taxes and borrowing, or that money is solely created by the central bank. Another motivation for this review comes in the context of the economic crises faced by countries like Pakistan that reel under currency depreciation, dependence on imports for food, medicines, and energy, and the unhelpful conditions stipulated by IMF loans. The idea is to explore whether MMT has any hope to offer such countries or whether it is predominately applicable to the U.S. whose dollar serves as the world reserve currency. Thus, the key ideas presented in this book are systematically delineated below.
Keywords: Modern Monetary Theory (MMT); economics; education